2022
DOI: 10.31557/apjcp.2022.23.1.271
|View full text |Cite
|
Sign up to set email alerts
|

New Approach about the Signaling Crosstalk between IQGAPs/ NF- κB/IL-8 and PDCD5/p53/TRAIL Pathways that Modulate Malignant Transformation in Hepatocellular Carcinoma

Abstract: and the third most common reason of cancer-related mortality (Sayiner et al., 2019). Due to the fact that most HCC patients have acquired cirrhosis, chemotherapy regimen or major resections are not efficiently tolerated (Wang et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…were independent risk factors of HCC [42]. IQGAP1 is known to be overexpressed in HCC [43]. Zhao et al and Lai et al reported that CDC20 as tumor promoters in HCC [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…were independent risk factors of HCC [42]. IQGAP1 is known to be overexpressed in HCC [43]. Zhao et al and Lai et al reported that CDC20 as tumor promoters in HCC [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…IQGAPs have attracted increasing interest in cancer research because of their fundamental contribution to cytoskeletal remodeling and signal transduction. Numerous studies have shown an association between IQGAPs and HCC initiation, metastasis, and recurrence, as well as poor prognosis in patients with HCC ( 10 , 16 24 , 29 , 81 , 90 98 ) (details in Table 1 ).…”
Section: The Relationship Between Iqgaps and Liver Diseasesmentioning
confidence: 99%
“…However, the mRNA expressions of members of Ras gene family significantly decreased after IQGAP1 silencing, which was accompanied by reduced proliferation and invasion ability of HCC cells ( 97 ). In addition, ERK and AKT may be involved in IQGAP1-induced elevation of NF-κB, promoting tumorigenesis, metastasis, and resistance to apoptosis ( 10 , 123 , 124 ). These results suggest that IQGAP1 may activate the MAPK/ERK signaling pathway by upregulating Ras gene family expression to promote hepatocarcinogenesis and progression.…”
Section: Action Mechanism Of Iqgaps In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…IQGAPs are considered to play a comprehensive and distinct role in HCC and therefore warrant more research to explore the concrete mechanisms of IQGAPs in HCC [10]. IQGAP1 has been shown to be upregulated in HCC as well as being involved in the oncogenic process [11][12][13][14][15]. Xu et al reported that IQGAP1 could interact with CDC42 to stimulate cell division, thus promoting the proliferation of HuH-7 cells [11].…”
Section: Introductionmentioning
confidence: 99%